INVESTIGATION OF THE EFFECT OF A PHYSIOTHERAPY AND REHABILITATION PROGRAM IN A CASE WITH CONGENITAL CENTRAL HYPOVENTILATION SYNDROME AND CEREBRAL PALSY: A CASE REPORT - Burak, Mustafa; Erturan, Sinem; Elbasan, Bulent (My University, 2024)
Congenital Central Hypoventilation Syndrome is a rare genetic disorder that presents from birth and prevents automatic control of respiration. Our aim in this study was to examine the effectiveness of a 6-month physical therapy program applied to a patient with Congenital Central Hypoventilation Syndrome and cerebral palsy. A 6-month-old patient who was diagnosed with Congenital Central Hypoventilation Syndrome and subsequently developed Cerebral Palsy due to asphyxia was included in the study. The case was enrolled in a physical therapy program for 2 days a week for 6 months in the home environment where they lived. The case was evaluated before and after treatment. In our case, the Modified Ashworth Scale, the Alberta Infant Motor Scale, the Hammersmith Infant Neurological Examination, Test of Sensory Functions in Infants, and the Face, Legs, Activity, Cry, Consol ability scale were used. In our case, pre-treatment and post-treatment scores were as follows, respectively: Alberta Infant Motor Scale score 3-8, Hammersmith Infant Neurological Examination score 6-17, Test of Sensory Functions in Infants score 2-9, and Face, Legs, Activity, Cry, Consol ability scale score 8-3. In our case, there was a significant improvement in Modified Ashworth Scale scores before and after treatment. Additionally, at the conclusion of the study, it was noted that the heightened pain and sensitivity resulting from the patient's extended stay in the intensive care unit reduced with the treatment. We believe that the administered physiotherapy and rehabilitation program offered support to the patient in achieving neuro-motor and sensory integration, underscoring the essential role of physiotherapy in rare diseases.
Keywords: Cerebral palsy; early intervention; congenital central hypoventilation syndrome